Mengenali pengaruh emosional pada suara manusia menggunakan metode Fast Fourier Transform (FFT) - Phita Aulia Ummami (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2019)
Emotion is a feeling that is felt by someone and can be addressed to other people or something and can arise as a reaction due to certain events. Some previous studies have stated that some statistical parameters have a high correlation between speech and emotional states that can indirectly influence the state of sound identified. In this study a simple experiment was carried out by taking nine samples with three different emotional characters namely sad, happy, and angry taken from three respondents who were randomly selected with the aim of identifying differences in emotions generated through sound data using the Fast Fourier Transform method ( FFT).